2021
DOI: 10.3389/fendo.2021.630097
|View full text |Cite
|
Sign up to set email alerts
|

NT3/TrkC Pathway Modulates the Expression of UCP-1 and Adipocyte Size in Human and Rodent Adipose Tissue

Abstract: Neurotrophin-3 (NT3), through activation of its tropomyosin-related kinase receptor C (TrkC), modulates neuronal survival and neural stem cell differentiation. It is widely distributed in peripheral tissues (especially vessels and pancreas) and this ubiquitous pattern suggests a role for NT3, outside the nervous system and related to metabolic functions. The presence of the NT3/TrkC pathway in the adipose tissue (AT) has never been investigated. Present work studies in human and murine adipose tissue (AT) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Accordingly, EV mice showed partially decreased basal hyperinsulinemia—a desirable feature for the treatment of obesity [ 59 ]. Additionally, we observed that miR-122 inhibition had a stronger effect in the sWAT, resulting in upregulation of direct target genes with beneficial effects on obesity—including Vav1 , whose knockout displayed increased fat content by decreasing Sirt1 activity [ 60 ]; or Ntrk3 , which promotes browning [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, EV mice showed partially decreased basal hyperinsulinemia—a desirable feature for the treatment of obesity [ 59 ]. Additionally, we observed that miR-122 inhibition had a stronger effect in the sWAT, resulting in upregulation of direct target genes with beneficial effects on obesity—including Vav1 , whose knockout displayed increased fat content by decreasing Sirt1 activity [ 60 ]; or Ntrk3 , which promotes browning [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…White and brown adipocytes grow larger when NT-3/TRKC signaling is disrupted, and UCP1 expression is reduced. 223 Through sympathetic nerve stimulation, exposure to cold may cause upregulation of S100 calcium-binding protein B (S100B) in inguinal adipocytes. By regulating PRDM16 and causing the expression of UCP1, upregulated S100B may cause WAT browning.…”
Section: Wat Endocrine Remodeling and Muomentioning
confidence: 99%
“…Blood vessels are the main source of NT‐3 release, which activates tropomyosin receptor kinase C (TRKC) to control adipocyte differentiation and browning. White and brown adipocytes grow larger when NT‐3/TRKC signaling is disrupted, and UCP1 expression is reduced 223 …”
Section: Interactions Between Different Types Of Adipose Tissue Remod...mentioning
confidence: 99%
“…20 But as the brain matures, the level of NT-3 will decrease sharply, so its endogenous function is limited. 21 Similarly, NT-4/5 plays a key role in cell survival and synaptic plasticity. 22 Relevant studies have proved that various neurotrophins can combine with tropomyosin-related kinase (Trk) receptor and p75 neurotrophic factor receptor (p75NTR) to exert their neurotrophic effects and regulate nerve inflammation and myelin sheath growth; meanwhile, it could modulate cell apoptosis, stimulate neuron survival, promote the maintenance of the CNS as well as neural functional recovery, and participate in repair after TBI injury.…”
Section: Mechanis M Of Neurotrophin S In Tb Imentioning
confidence: 99%
“…In the development of CNS, NT‐3 is involved in the growth of neural connections and the formation of synapses, and NT‐3 is superior to NGF or BDNF in promoting axon regeneration 20 . But as the brain matures, the level of NT‐3 will decrease sharply, so its endogenous function is limited 21 . Similarly, NT‐4/5 plays a key role in cell survival and synaptic plasticity 22 …”
Section: Mechanism Of Neurotrophins In Tbimentioning
confidence: 99%